2017
DOI: 10.19173/irrodl.v18i7.3155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the UNED MOOCs Implementation: Demographics, Learners' Opinions and Completion Rates

Abstract: The paper is a study about the MOOC experience at the Spanish National University of Distance Education (UNED), where we have collected initial and final information about learners' profiles and opinions, as well as enrolment, completion and certification rates. It is a survey-based study covering 17 MOOCs offered in UNED's own platform, and collects information from a sample of more than 24000 learners (initial survey) and 2003 learners (final survey). The paper first presents an overview of the MOOC experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In spite of the numerous studies conducted to study learner motivations for enrolling in MOOCs (Belanger & Thornton, 2013;Gil-Jaurena, Callejo-Gallego, & Agudo, 2017;Konstan et al, 2015;Macleod, Haywood, Woodgate, & Alkhatnai, 2014;Radford, Coningham, & Horn, 2015;Zhong, Zhang, Li, & Liu, 2016), only a few of them have investigated the influence of motivation on MOOC completion. Konstan, Walker, Brooks, Brown, and Ekstrand (2015) concluded that most of the reasons that learners enrolled in a MOOC, such as university/instructor-related reasons or access to educational institutions-related reasons, did not affect course completion, but that learners' self-reported intention of completing the MOOC was a significant predictor of course completion.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the numerous studies conducted to study learner motivations for enrolling in MOOCs (Belanger & Thornton, 2013;Gil-Jaurena, Callejo-Gallego, & Agudo, 2017;Konstan et al, 2015;Macleod, Haywood, Woodgate, & Alkhatnai, 2014;Radford, Coningham, & Horn, 2015;Zhong, Zhang, Li, & Liu, 2016), only a few of them have investigated the influence of motivation on MOOC completion. Konstan, Walker, Brooks, Brown, and Ekstrand (2015) concluded that most of the reasons that learners enrolled in a MOOC, such as university/instructor-related reasons or access to educational institutions-related reasons, did not affect course completion, but that learners' self-reported intention of completing the MOOC was a significant predictor of course completion.…”
Section: Introductionmentioning
confidence: 99%
“…The first part included similar questions found in other moocs at uned Abierta to obtain data regarding students' initial intentions, and therefore, test validity was confirmed. The second part of the questionnaire, at the end of the course, included common questions found in other uned mooc to test students' satisfaction with respect to course contents (Gil-Jaurena et al, 2017). In addition, we also included similar questions to those found in the first part of the questionnaire to test whether respondents' initial intentions were reaffirmed after taking the mooc.…”
Section: Methodsmentioning
confidence: 99%
“…A common approach is to use questionnaires on the user experience. A study about the MOOC experience at the Spanish National University of Distance Education used surveys covering 17 MOOCs offered by the university's own platform to analyse completion rates and the overall user experience (Gil-Jaurena et al, 2017). For an Australian study, conducted in cooperation with the OpenLearning platform, an evaluation form was embedded directly into the MOOCs to collect and analyse participants' attitudes and the perceived usefulness (Rawlings et al, 2017).…”
Section: State Of the Artmentioning
confidence: 99%